(untitled) (Journal of the College of Basic Education, 2022)
The research included five chapters: The first chapter included the introduction and the importance of the research, as the introduction dealt with the meansAnd training methods in helping researchers, scholars and those in charge of the training process inThe field of sports training to change the old means and methods dependent on them, to adoptModern scientific methods, according to our codified method, lead to knowledge of the impact of training on the development of manyFunctional and skill indicators. Skills are the basis for learning any game that has become fromIt is necessary to think about preparing some compound exercises to develop some motor skillsFootball is an exciting and popular game. The junior stage is one of the most important stages